Supports and Interventions for Carers of a Person with Depressive or Anxiety Symptomology: A Systematic Review - Elloyse Fitzgeraldson; Frances Kay-Lambkin; Natasha Harding; Kimie M. McNaughton; Zoi Triandafilidis; Jacinta Heath; Bronte Lyford; Janine Charnley; Sally Fitzpatrick (Europe's Journal of Psychology, 2022)
An increasing body of research attests to the capacity of evidence-based interventions to improve outcomes for informal carers. A review of suitable supports and interventions for carers of a person with depressive or anxiety symptomology is timely. This systematic review explores intervention suitability evidence for this carer group. Searches for relevant primary studies were conducted in six databases across a 15-year timeframe (October 2004–October 2019). Studies were assessed and compared narratively and thematically. Qualitative themes were synthesised with quantitative studies to explore the extent to which carer preferences were embedded in interventions. The initial literature search produced 13,183 studies. Six studies—three randomised controlled trials (RCTs) and three mixed-method studies—were included following a double-blinded screening process, a review of reference lists and risk of bias assessment. Included studies contributed either intervention efficacy or acceptability evidence. The synthesis of qualitative themes with quantitative studies found that carer-specific needs and targeted psychoeducation were featured in interventions from all six quantitative studies. Current evidence for appropriate supports and interventions for this carer group is limited. The review uncovers a lack of interventions for carers of a person with anxiety symptomology and limited intervention suitability evidence for carers of a person with depressive symptomology. More research is needed to explore the needs and preferences of this carer group, and how best to support them.